Community food hubs: an economic and social justice model for regional Australia?. Issue 3 (2nd September 2017) - Rose, Nicholas
ABSTRACT: Community food hubs expand market access for small to medium-sized farmers and enhance producer viability and capacity. They also have the potential to create jobs, strengthen local and regional economies, build resilience, increase access to healthy food and support the necessary transition to sustainable agriculture. From less than a dozen existing 15 years ago, there are now more than 350 food hubs across the United States which are part of a booming local food sector worth in excess of $US12 billion annually. To support the emergence of these enterprises in Australia, an inaugural Australian community food hubs conference and speaking tour occurred in August 2016, with international speakers attending from the United States and Canada. By conducting a critical literature review, further informed from participant observation, this article analyses the opportunities and challenges for the development and expansion of a food hub sector in regional Australia.